Bax-inhibiting peptides derived from Ku70 and cell-penetrating pentapeptides. (20th July 2007) - Gomez, J.A.; Gama, V.; Yoshida, T.; Sun, W.; Hayes, P.; Leskov, K.; Boothman, D.; Matsuyama, S.
Abstract : We found that Ku70, a known DNA repair factor, has a novel function to bind and inhibit Bax (Bcl-2-associated X protein), a key mediator of apoptosis. Pentapeptides derived from the Bax-binding domain of Ku70 were cell-permeable and protected cells from Bax-mediated apoptosis. These pentapeptides were called BIPs (Bax-inhibiting peptides). BIPs may become a useful therapeutic tool to reduce cellular damage. We also generated BIP mutant pentapeptides that do not inhibit Bax, but retain their cell-penetrating activity. Since both BIPs and BIP mutants are cell-permeable, these peptides were designated CPP5s (cell-penetrating pentapeptides). Among the CPP5s discovered, VPTLK (BIP) and KLPVM (BIP mutant) were confirmed to possess protein transduction activity by examination of the delivery of GFP (green fluorescent protein) into cells by these peptides. The mechanism of cell penetration by CPP5s is not known. CPP5s enter the cell at 0 and 4°C. In preliminary studies, various inhibitors of endocytosis and pinocytosis did not show any significant suppression of CPP5 cell entry. CPP5s have very low toxicity in vitro and in vivo and so may be useful tools in order to develop non-toxic drug-delivery technologies.